UPAYA PENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR AKUNTANSI MELALUI PEMBELAJARAN TIPE NUMBERED HEAD TOGETHER - Hidayati, Muzayyanah; Susilaningsih, -; Hamidi, Nurhasan (Jupe-Jurnal Pendidikan Ekonomi, 2013)
ABSTRAK Tujuan penelitian ini untuk meningkatkan motivasi belajar dan prestasi belajar akuntansi dengan menerapkan model pembelajaran NHT siswa kelas XI IPS di sebuah SMA Surakarta tahun pelajaran 2012/2013. Penelitian ini menggunakan pendekatan Penelitian Tindakan Kelas. Subjek penelitian adalah siswa kelas XI IPS 2 di sebuah SMA Surakarta yang berjumlah 32 siswa. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran NHT dapat meningkatkan motivasi belajar dan prestasi belajar akuntansi siswa kelas XI IPS di sebuah SMA Surakarta. Hal ini dapat dilihat dari beberapa indikator sebagai berikut: (1) Penerapan model pembelajaran kooperatif tipe Numbered Head Together pada indikator motivasi belajar siswa mengalami kenaikan sebesar 12,50% yang mulanya 68,43% pada siklus I menjadi 80,93% pada siklus II, (2) indikator keaktifan siswa dalam bertanya mengalami peningkatan dari 43,75% pada siklus I menjadi 71,87% pada siklus II, (3) indikator keaktifan siswa dalam diskusi mengalami peningkatan dari 43,75% pada siklus I menjadi 75% pada siklus II, dan (4) prestasi belajar menunjukkan peningkatan ketuntasan dari 62,50% pada siklus I menjadi 82,25% pada siklus II. kata kunci: numbered head together, motivasi belajar, prestasi belajar   ABSTRACT The objectives of this research are to improve the learning motivation and the learning achievement in Accounting of the students in Grade XI of Social Science Program of Senior Secondary School of Surakarta in Academic Year 2012/2013. The research used the classroom action research. The subject of the research were the students in Grade XI of Social Science Program 2 of a Senior Secondary School of Surakarta as many as 32 students. The results of the research show that the application of the learning model of NHT can improve the learning motivation and the learning achievement in Accounting of the students in Grade XI of Social Science Program 2 of a Senior Secondary School of Surakarta. This is indicated by several indicators as follows: 1) There is an increase of 12.50% in the learning motivation of the students. The percentage of their learning motivation is 68.43% in Cycle I, and it becomes 80.93% in Cycle II. 2) There is an increase in the activeness of the students to raise questions. The percentage of their activeness to raise questions is 43.75% in Cycle I, and it becomes 71.87% in Cycle II. 3) There is an increase in the activeness of the students in discussion. The percentage of their activeness in discussion is 43.75% in Cycle I, and it becomes 75% in Cycle II. 4) There is an increase in the classical learning completeness of the students as indicated by their learning achievement. The number of the students to complete their classical learning is (62.50%) in Cycle I, and it becomes (82.25%) in Cycle II. Keywords: numbered head together, learning motivation and learning achievement.